Spare the rod, spoil the child: measurement and learning from an intervention to shift corporal punishment attitudes and behaviors in Grenada, West Indies - Landon, Barbara; Thomas, Elizabeth D.; Orlando, Lauren; Evans, Roberta; Murray, Toni; Mohammed, Lauren; Noel, Jesma; Isaac, Rashida; Waechter, Randall (Frontiers in Public Health, 2023)
Childrearing practices in the Caribbean and other postcolonial states have long been associated with corporal punishment and are influenced by expectations of children for respectfulness and obedience. Evidence across settings shows that physical punishment of young children is both ineffective and detrimental. Saving Brains Grenada (SBG) implemented a pilot study of an intervention based on the Conscious Discipline curriculum that aimed to build adult caregivers’ skills around non-violent child discipline. We hypothesized that attitudes towards corporal punishment would shift to be negative as adults learned more positive discipline methods, and that child neurodevelopment would correspondingly improve. This report reviews the impact of monitoring and evaluation on the design and implementation of the intervention. Study 1 presents findings from the pilot study. Despite positive gains in neurodevelopmental outcomes among children in the intervention compared to controls, attitudes towards corporal punishment and reported use of it did not change. Additionally, several internal conflicts in the measures used to assess corporal punishment behaviors and attitudes were identified. Study 2 is a response to learning from Study 1 and highlights the importance for monitoring and evaluation to be data-informed, adaptive, and culturally appropriate. In Study 2, the SBG research team conducted cognitive interviews and group discussions with stakeholders to assess the content and comprehensibility of the Attitudes Towards Corporal Punishment Scale (ACP). This yielded insights into the measurement of attitudes towards corporal punishment and related parenting behavior, and prompted several revisions to the ACP. To accurately evaluate the intervention’s theory of change and its goal to reduce violence against children, reliable and appropriate measures of attitudes towards corporal punishment and punishment behaviors are needed. Together, these two studies emphasize the value of continuous monitoring, evaluation, and learning in the implementation, adaptation, evaluation, and scaling of SBG and similar early childhood development interventions.